Plasmonic nanopipette biosensor - Masson, Jean-François; Breault-Turcot, Julien; Faid, Rita; Poirier-Richard, Hugo-Pierre; Yockell-Lelièvre, Hélène; Lussier, Félix; Spatz, Joachim P. (Analytical chemistry, 2014)
Integrating a SERS immunoassay on a plasmonic “patch clamp” nanopipette enabled nanobiosensing for the detection of IgG. A SERS response was obtained using a sandwich assay benefiting from plasmon coupling between a capture Au nanoparticle (AuNP) on a nanotip and a second AuNP modified with a Raman active reporter and an antibody selective for IgG. The impact of nanoparticle shape and surface coverage was investigated alongside the choice of Raman active reporter, deposition pH, and plasmonic coupling, in an attempt to fully understand the plasmonic properties of nanopipettes and to optimize the nanobiosensor for the detection of IgG. These probes will find applications in various fields due to their nanoscale size leading to the possibility of spatially and temporally addressing their location near cells to monitor secretion of biomolecules.